A Low‐Cost, Small Volume Circuit for Autologous Blood Normothermic Perfusion of Rabbit Organs. Issue 4 (27th August 2013) - Worner, Murray; Poore, Samuel; Tilkorn, Daniel; Lokmic, Zerina; Penington, Anthony J.
Abstract We have designed a laboratory extracorporeal normothermic blood perfusion system for whole organs (e.g., kidney) that achieves pulsatile flow, low levels of hemolysis, and a blood priming volume of 60 mL or less. Using this uniquely designed extracorporeal circuit, we have achieved perfusion of two isolated ex vivo constructs. In the first experiment, we successfully perfused a rabbit epigastric flap based on the femoral vessels. In the second experiment, we were able to perfuse the isolated rabbit kidney for 48 h (range for all kidneys was 12–48 h) with excellent urine output, normal arterial blood gasses at 24 h, and normal ex vivo kidney histology at the conclusion of the experiments. These parameters have not been achieved before with any known or previously published laboratory extracorporeal circuits. The study has implications for prolonged organ perfusion prior to transplantation and for tissue engineering of vascularized tissues, such as by the perfusion of decellularized organs.